2020
DOI: 10.1101/2020.05.26.117499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Context matters: Situational stress impedes functional reorganization of intrinsic brain connectivity during problem solving

Abstract: Extensive research has established the relationship between individual differences in brain activity in a resting state and individual differences in behavior. Conversely, when individuals are engaged in various tasks, certain task-evoked reorganization occurs in brain functional connectivity, which consequently can influence individuals' performance as well. Here, we show that resting state and task-dependent state brain patterns interact as a function of contexts engendering stress. Findings revealed that wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Previous research has shown that SBS contexts typically engender a variety of behavioral and physiological SBS responses including sustained vACC activation, unique neural network configurations, and enhanced connectivity between regions integral for emotion (dACC, vACC, and mPFC) and saliency networks (IPL, insula, and STS). This evidence collectively suggests increased emotional processing and heightened awareness of negatively arousing or stressful information (Forbes et al, 2018;Liu et al, 2020Liu et al, , 2021Amey et al, 2022). We sought to understand if threatened women can transmit their stress to otherwise non-threatened partners, does it hurt or benefit the woman directly under threat, and to what extent can this come at a cost to their otherwise non-threatened partners?…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that SBS contexts typically engender a variety of behavioral and physiological SBS responses including sustained vACC activation, unique neural network configurations, and enhanced connectivity between regions integral for emotion (dACC, vACC, and mPFC) and saliency networks (IPL, insula, and STS). This evidence collectively suggests increased emotional processing and heightened awareness of negatively arousing or stressful information (Forbes et al, 2018;Liu et al, 2020Liu et al, , 2021Amey et al, 2022). We sought to understand if threatened women can transmit their stress to otherwise non-threatened partners, does it hurt or benefit the woman directly under threat, and to what extent can this come at a cost to their otherwise non-threatened partners?…”
Section: Introductionmentioning
confidence: 99%